Supplementary dydrogesterone is beneficial as luteal phase support in artificial frozen-thawed embryo transfer cycles compared to micronized progesterone alone - Vidal, Angela; Dhakal, Carolin; Werth, Nathalie; Weiss, Jürgen Michael; Lehnick, Dirk; Kohl Schwartz, Alexandra Sabrina (Frontiers in Endocrinology, 2023)
The number of frozen embryo transfers increased substantially in recent years. Maturation of the endometrium is facilitated by sequential administration of estrogens, followed by administration of progesterone prior to embryo transfer. The use of progesterone is crucial for pregnancy outcomes. This study compares the reproductive outcomes and tolerability of five different regimens of hormonal luteal phase support in artificial frozen embryo transfer cycles, with the objective of determining the best progesterone luteal phase support in this context. This is a single-center retrospective cohort study of all women undergoing frozen embryo transfers between 2013 and 2019. After sufficient endometrial thickness was achieved by estradiol, luteal phase support was initiated. The following five different progesterone applications were compared: 1) oral dydrogesterone (30 mg/day), 2) vaginal micronized progesterone gel (90 mg/day), 3) dydrogesterone (20 mg/day) plus micronized progesterone gel (90 mg/day) (dydrogesterone + micronized progesterone gel), 4) micronized progesterone capsules (600 mg/day), and (5) subcutaneous injection of progesterone 25 mg/day (subcutan-P4). The vaginal micronized progesterone gel application served as the reference group. If the endometrial thickness was ≥7 mm, luteal phase support was started. The primary outcome was the clinical pregnancy rate. In total, 391 cycles were included in the study (median age of study participants 35 years). Differences among the five groups in other baseline characteristics were not significant. Multiple logistic regression analysis, adjusting for pre-defined covariates, showed that the clinical pregnancy rates were higher in the oral dydrogesterone only group (OR = 2.87, 95% CI 1.38–6.00, p=0.005) and in the dydrogesterone + micronized progesterone gel group (OR = 5.19, 95% CI 1.76–15.36, p = 0.003) compared to micronized progesterone gel alone. The live birth rate was higher in the oral dydrogesterone-only group (OR = 2.58; 95% CI 1.11–6.00; p=0.028) and showed no difference in the smaller dydrogesterone + micronized progesterone gel group (OR = 2.49; 95% CI 0.74–8.38; p=0.14) compared with the reference group. The application of dydrogesterone in addition to micronized progesterone gel was associated with higher clinical pregnancy rate and live birth rate and than the use of micronized progesterone gel alone.